2020
DOI: 10.1093/eurpub/ckaa166.608
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: knowledge and attitudes of hospital staff of a large Italian teaching hospital

Abstract: Background During infectious disease emergencies, fully aware healthcare workers (HCWs) and public services staff are unique resources to keep health systems active and tackle epidemics. Aim of the study was to assess concern, general and health-related knowledge (case management and Infection Prevention and Control [IPC] measures) among hospital staff on SARS-CoV-2 in Lombardy region (Italy). Methods One week after WHO decla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
4
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 0 publications
5
25
4
11
Order By: Relevance
“…In addition, it was found that physicians answered the questions about propositions relating to COVID-19 more accurately than nurses. Among studies evaluating the knowledge of healthcare professionals during the outbreak, the level of knowledge of physicians was found to be higher in this study than in studies conducted not only on physicians and nurses but also on heterogeneous groups with less direct contact with patients, such as administrative staff, pharmacists, dentists, and technicians [ 5 , 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, it was found that physicians answered the questions about propositions relating to COVID-19 more accurately than nurses. Among studies evaluating the knowledge of healthcare professionals during the outbreak, the level of knowledge of physicians was found to be higher in this study than in studies conducted not only on physicians and nurses but also on heterogeneous groups with less direct contact with patients, such as administrative staff, pharmacists, dentists, and technicians [ 5 , 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Among the three themes, pandemic related knowledge was most studied, followed by practices and attitudes (Tables 2-4). In the knowledge domain, symptoms (13, 14, 16, 22-69), transmission (14, 16, 22, 23, 25-29, 31-34, 37-49, 51, 52, 55-57, 59-78) and incubation period of the virus (16, 23, 26-28, 32, 37, 38, 41, 42, 46-50, 52-57, 59-64, 66-69, 78); management and treatment options (14, 16, 22-24, 26, 27, 29, 37, 39-43, 46, 48-51, 55, 56, 58, 60, 62, 64, 66-70, 78, 79); and clinical outcomes associated with infection (13, 16, 23-27, 29, 34, 37, 38, 40, 48, 50-52, 55, 56, 59, 61, 63-67, 69, 74-76, 78-81); high risk populations for infection (16, 23, 26, 27, 29,…”
Section: Resultsmentioning
confidence: 99%
“…A previous study sample was considered with a total number of 2,045 participants, which indicates the number of samples taken in that survey. 22 The sampling method employed here is the simple random sampling method. For the data collection and tabulation, the questionnaire validity checking was done by consulting an expert.…”
Section: Methodsmentioning
confidence: 99%